1994
DOI: 10.1111/j.1365-2265.1994.tb02589.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone releasing activity by intranasal administration of a synthetic hexapeptide (hexarelin)

Abstract: The synthetic hexapeptide hexarelin is a potent pituitary GH stimulator when administered intranasally. The GH response was similar to that observed after intravenous hexarelin. Simultaneously, there was a significant decrease in plasma TSH but the concentrations remained in the normal range. These findings appear to be of theoretical and practical relevance to the investigation and management of short children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 10 publications
(10 reference statements)
1
16
0
Order By: Relevance
“…The short-and long-term activity of the GHRPs, even when administered orally or intranasally (2,3,5,11), make them potentially superior to GHRH, whose use is restricted to injections (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The short-and long-term activity of the GHRPs, even when administered orally or intranasally (2,3,5,11), make them potentially superior to GHRH, whose use is restricted to injections (8).…”
Section: Discussionmentioning
confidence: 99%
“…Our group has demonstrated that hexarelin is a very potent stimulant of growth hormone (GH) release also in children (3,4), and long-term intranasal adminis¬ tration to short children induces an increase in serum IGF-I levels, anabolic metabolic changes and an acceleration of linear growth (5).…”
mentioning
confidence: 99%
“…Intravenous ghrelin administration has not affected TSH blood levels in humans [36]. On the other hand, a well-known synthetic ghrelin analog, hexarelin, when applied intravenously or intranasally to GH-deficient patients, decreased TSH plasma levels, without affecting free T 4 and T 3 plasma levels in both tests [37]. The discrepancy between the studies may be explained by different experimental protocols, including variances in the duration of treatment (single or repetitive versus chronic treatment effects), route of administration (ICV versus intraperitoneal treatment effects), and/or applied dose.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical efficacy and specificity of the GHRPs in elevating GH have been established (6) and more recently GH release in humans has been reported by using the GHRP-6 analog hexarelin (7,8). Furthermore, the nonpeptide L-692,429 (MK-0751) ( Fig.…”
mentioning
confidence: 99%